ECOCRITICAL AWARENESS IN THE NOVEL ANIMAL’S PEOPLE BY INDRA SINHA - Ridha Ikhva Erviana; Yuliana Triyani (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study aims to depict the ecological crisis and the portrayal of environmental awareness in Indra Sinha's novel Animal's People (2007), set against the backdrop of a devastating chemical accident. The research examines how the novel's characters, who are victims of the disaster navigate their disrupted lives while grappling with the environmental chaos that occurs. Through the lens of Greg Garrard's (2004) ecocriticism and ecology theory, this qualitative analysis delves into three distinct forms of environmental awareness: pastoral, wilderness, and dwelling. These concepts are used to unravel how the novel critiques industrial society's impact on nature and advocates for a deeper, more harmonious relationship between humans and their environment. The findings reveal that the characters' struggles are not just for survival but also for reclaiming their connection with the natural world, which has been severely compromised by the disaster. This study highlights the novel's powerful commentary on the urgent need to address environmental degradation and the social injustices intertwined with ecological issues, emphasizing the importance of preserving the surroundings for future generations.